ANALISIS PENGARUH CURRENT RATIO (CR), UKURAN PERUSAHAAN DAN DEBT TO EQUITY RATIO (DER) TERHADAP PROFITABILITAS PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021–2024 - Simbolon, Frentiani Revalina; br Ambarita, Gmandys Anggi Wella; Purnasari, Nina; Herliani, Rini (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to obtain information on whether the current ratio, company size, and debt to equity ratio simultaneously or partially affect return on assets in LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. The independent variables are CR, Company Size, and DER. The dependent variable is Return on Assets. This study uses a quantitative approach, data analysis is obtained through statistical analysis. The method used to analyze the research results is multiple linear regression. There are 45 populations with 20 samples, a total of 80 observation data (20x4). The results show that CR, Company Size, and DER simultaneously influence Return on Assets. Partially, CR and DER have a positive and significant effect on Return on Assets, while Company Size has a negative and significant effect on Return on Assets in LQ45 companies listed on the IDX for the 2021-2024 period. This study shows that the results of the determination coefficient test have an Adjusted R Square value of 0.179 indicating that the CR, Company Size, and DER variables are able to explain variations in ROA by 17.9%, while the remaining 82.1% is influenced by other variables outside the research model